Mental models in the perception of the relationship between climate and production systems in Caquetá, Colombia - Lopez, Maria Claudia; Alvarez, Javier; Rodriguz, Luz Angela; Vanegas Cubillos, Martha (2024)
This document presents the results of small cocoa and livestock producers’ perception, based on their mental models, regarding the changes they observe in climate and the adaptation and mitigation actions they are implementing on their farms, and those they believe are necessary to address the challenges related to climate change. Mental models are the representations that cognitive systems create to interpret the environment and its different functions, constituting a strategy that allows us to understand the knowledge that different human groups may have about the causes, consequences, and solutions to specific problems.